Maritime Culture Degradation of Indonesian Society in Social Practice of Seafaring - Aini Nahdlia Puspita; Widodo Widodo; Abdul Rivai Ras; Pujo Widodo; Herlina Juni Risma Saragih (CV. Rayyan Dwi Bharata, 2023)
Indonesia since a long time ago has been known as a nation whose maritime is very strong, such as the activities or practices of seafaring which were carried out by the ancestors of the Indonesian nation. However, the current problem is the degradation of maritime culture in the social practices of seafaring. The purpose of this research is to find out the factors that cause Indonesian people not to go to sea and the degradation of maritime culture that occurs in Indonesian society in the social practices of seafaring. The method used in this study is a qualitative descriptive method with data sources derived from relevant books or journals. The results of this study, namely (1) the factors that cause people not to go to sea are due to unstable social economy for fisherman, climate change and erratic weather, fuel oil (BBM) which is difficult to obtain for ships, the use of technology that is still old technology, and the quota-based fisheries policy; and (2) the current degradation of maritime culture in Indonesian society is the transition from fisherman to other professions, such as farmers, foreign ship crews, and Indonesian migrant workers.